2022
DOI: 10.3389/fvets.2022.984634
|View full text |Cite
|
Sign up to set email alerts
|

Rumen microbiota responses to the enzymatic hydrolyzed cottonseed peptide supplement under high-concentrate diet feeding process

Abstract: In current dairy production, dietary energy is always excessively provided with a high-concentrate diet feeding to improve milk production. However, this feeding practice disturbed the rumen microbial ecosystem and the balance between ruminal energy and nitrogen, resulting in decreased nutrient fermentability, which in turn declined the milk yield of dairy cows. Therefore, supplementation of dietary degradable nitrogen may be helpful for high dairy production. In this study, we evaluated the regulatory effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Ammonia nitrogen is the main nitrogen source for rumen microbial fermentation and an important indicator affecting microbial activity. Suitable ammonia nitrogen is the primary condition to ensure the efficiency of microbial protein synthesis ( 25 , 26 ). The concentration of ammonia nitrogen and volatile fatty acid (VFA) in the rumen are important indicators reflecting the fermentation status of feed in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…Ammonia nitrogen is the main nitrogen source for rumen microbial fermentation and an important indicator affecting microbial activity. Suitable ammonia nitrogen is the primary condition to ensure the efficiency of microbial protein synthesis ( 25 , 26 ). The concentration of ammonia nitrogen and volatile fatty acid (VFA) in the rumen are important indicators reflecting the fermentation status of feed in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…The pH is affected by the feeding method, the concentrate-to-forage ratio and the dry matter content, and a substantial decrease in the rumen pH is the most common feature in the rumen of ruminants fed high-concentrate diets. Many studies have found that a decrease in pH to approximately 6.0, after animals regularly ingest a high-grain diet, results in a slight decrease in the fiber decomposition rate; however, the number of fibrolytic bacteria is usually unaffected, and a decrease to 5.5 or 5.0 results in a decrease in both the fiber decomposition rate and the number of fibrolytic bacteria, which may severely inhibit fiber digestion altogether, thus altering the rumen fermentation function [24,25]. In this study, the pH of the H2 group decreased sharply with feeding time and reached a minimum value of 5.44 after 2 h of feeding.…”
Section: Discussionmentioning
confidence: 99%